Certification through the lenses of environmental protection: lessons from the search of international conservation of forests - Megale, Tiago Matsuoka (2021)
The present dissertation is inserted in the broad scenario of international trade in which tariffs are low and non-tariff barriers to trade, also known as regulatory barriers, constitute the main obstacles to free trade. Among the regulatory barriers to trade currently debated, technical regulations, private standards and conformity assessment procedures, the last ones will be analyzed. Against the background of the paradigm of sustainable development, certification, the most common form of conformity assessment, allows the evaluation of the conformity with technical regulations and private standards in order to determine environment and consumption requirements of the product examined. Environmental requirements fall on wood and its derivatives that are tradable environmental goods that undergo forest certification, the focus of this dissertation. Forest certification is initially conceived as an alternative to the limited enforcement of international environmental treaties on forest issues and to the inability to conclude them in the area of international forest protection. After, shortcomings of forest certification are identified, namely the overlapping requirements presented by forest certifiers and the different degrees of environmental and social protection that they seek to achieve. The last shortcoming constitutes the research problem of this dissertation. In face of this problem, the question that drives this research is the following: can environmental certification demonstrate conformity with environmental standards and technical regulations and establish a common high level of forest protection to be attained? The hypothesis to be tested is as follows: environmental certification on the forest sector is operative worldwide, but created according to the interests of the civil society and multinational industrial corporations. The objective of this dissertation is to analyze the extent to which forest certification is guided by the economic, environmental, social and good governance pillars of sustainable development and is free from the economic bias towards unsustainable forest exploitation and utilization. The methodology implemented in this dissertation is bibliographical, descriptive and exploratory. This methodology allowed the understanding of the birth of forest certifiers that operated on the international level, of their conflicts during the certification wars and of the remaining competition between the two certifiers that continued internationally operative, Forest Stewardship Council (FSC) and Programme for the Endorsement of Forest Certification (PEFC). These phenomena were analyzed through the lenses of non-state market driven governance and of the regulator-intermediary-target framework. The dissertation then moved to the analysis of certification regulation on the multilateral trade system and on the regional European Union (EU) level, of forests in hard law and soft law and of forest certification. Lastly, the effectiveness of forest certification was analyzed based on the parameters of accreditation and mutual recognition. This dissertation concludes that, in terms of level of environmental protection derived from forest certification, the FLEGT Action Plan is a promising regulatory initiative that dialogues with forest certification standards through their incorporation in EU sustainable public procurement policies and that an analysis that combines FSC and PEFC regulation, its underpinning standards and the parameters of accreditation and mutual recognition allows the identification of the level of forest protection that the two international forest certifiers achieve. Lastly, research agendas are proposed based on the results obtained.